Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/antibiotics10010033
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus crispatus BC1 Biosurfactant Delivered by Hyalurosomes: An Advanced Strategy to Counteract Candida Biofilm

Abstract: The emergence of resistance to antifungal drugs has made the treatment of vulvovaginal candidiasis (VVC) very challenging. Among natural substances, biosurfactants (BS) produced by Lactobacillus have gained increasing interest in counteracting Candida infections for their proven anti-adhesive properties and safety profile. In the present study, liposomes (LP-BS) or liposomes coated with hyaluronic acid (HY-LP-BS) were prepared in the presence of the BS isolated from the vaginal strain Lactobacillus crispatus B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…In previous works, we highlighted the antimicrobial activity of L. crispatus BC1 fractions (i.e., lactobacilli cells and cell-free supernatant) against several urogenital and STI pathogens, such as Candida spp., C. trachomatis , Neisseria gonorrhoeae , and Streptococcus agalactiae [ 6 , 7 , 8 , 23 , 28 ]. Moreover, L. crispatus BC1-derived BS was recently indicated as a promising safe agent able to interfere with important Candida virulence factors, i.e., adhesion to cervicovaginal cells and biofilm formation [ 20 , 25 ]. In this context, our data added knowledge on the functions of lactobacilli-isolated BS, shedding light on new antimicrobial mechanisms and opening the way to the use of BS as an innovative and antibiotic-sparing anti-chlamydial strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous works, we highlighted the antimicrobial activity of L. crispatus BC1 fractions (i.e., lactobacilli cells and cell-free supernatant) against several urogenital and STI pathogens, such as Candida spp., C. trachomatis , Neisseria gonorrhoeae , and Streptococcus agalactiae [ 6 , 7 , 8 , 23 , 28 ]. Moreover, L. crispatus BC1-derived BS was recently indicated as a promising safe agent able to interfere with important Candida virulence factors, i.e., adhesion to cervicovaginal cells and biofilm formation [ 20 , 25 ]. In this context, our data added knowledge on the functions of lactobacilli-isolated BS, shedding light on new antimicrobial mechanisms and opening the way to the use of BS as an innovative and antibiotic-sparing anti-chlamydial strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Biosurfactants (BS) are amphiphilic compounds produced by microorganisms, anchored on the surface or secreted to the outside, with useful physicochemical and biological properties [15,16]. Among all their critical functions and applications, BS and particularly lactobacilli-derived BS have shown promising effects as antimicrobial molecules, both against bacteria and fungi [17][18][19][20]. Since Lactobacillus crispatus plays a crucial role in maintaining vaginal eubiosis [21], BS from this species could represent novel therapeutic agents to counteract CT infection.…”
Section: Introductionmentioning
confidence: 99%
“…overgrowth and reduce vulvovaginal candidiasis occurrence (Parolin et al, 2015;De Gregorio et al, 2019;Namarta et al, 2020). Anti-Candida activity of lactobacilli can be mediated through multiple mechanisms, including pH lowering, secretion of effective compounds, and impairment of fungal adhesion (Parolin et al, 2015(Parolin et al, , 2021Calonghi et al, 2017;Abruzzo et al, 2018Abruzzo et al, , 2021De Gregorio et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies had reported that supernatants of different Lactobacillus species can generate biosurfactants (e.g. dipalmitin, mevalonolactone, 1,5-monolinolein, distearin, 5-methyl-hydantoin), derivatives of butyric acid, autoinducer type 2 precursors including lower molecular compounds which previously demonstrated to exert a notable antimicrobial, antifungal and anti-biofilm inhibitory activity [17][18][19].…”
Section: Probiotic Oral and Vaginal Intercalation With The Women's Healthmentioning
confidence: 99%